Creating a Framework for Examining Federal Agency Rules Impacting Arbitration - Kristen M. Blankley (Washington University Journal of Law & Policy, 2020)
Since 1985, the analysis for determining how to resolve a conflict between the Federal Arbitration Act (“FAA”) and another federal statute has been clear – courts should consider whether Congress evidenced a “contrary congressional command” stating that arbitration agreements may not be enforced under the statute. In contrast, no court has created an analytical framework to consider how to compare federal regulatory actions (by rule or adjudication) prohibiting enforcement of pre-dispute arbitration agreements. This Article fills the gap and suggests two frameworks under which agency actions prohibiting enforcement of arbitration agreements could be considered a “contrary congressional command” rule focused on the enabling legislation or a “contrary regulatory command” rule focused on the regulation itself. Although both rules can be supported by public policy, the “contrary congressional command” rule more closely applies current arbitration law to this new context of regulatory actions. This Article traces the origins of the “contrary congressional command” rule and demonstrates how that rule can be used in cases involving agency action. This Article also gives concrete examples of how the different frameworks would lead to different results depending on the statutory language at issue, the agency action, and the conceptual framework chosen to analyze the case.
Keywords: Federal Arbitration Act; FAA; arbitration agreement; contrary congressional command; federal law